The study of demand response programs for economic dispatch in multiple time steps - Eynon, Rachael (2018)
This project investigates the application of Demand Response (DR) within an electricity market model. Many existing studies make use of piecewise linear curve fitting for a simplified representation of demand and supply bids in the network. By using quadratic generator cost functions and consumer benefit functions, an accurate market model incorporating demand response can be developed. This report presents an evaluation of the effectiveness of demand response within the market model and quantifies the savings that can be made.